Sharing model uncertainty - Chiaki Hara; Sujoy Mukerji; Frank Riedel; Jean-Marc Tallon (Queen Mary University of London, School of Economics and Finance, 2025)
This paper examines efficient allocations in economies where consumers exhibit heterogeneous smooth ambiguity preferences and face model uncertainty with a common set of identifiable models. Aggregate endowment is ambiguous. We characterize economies where the representative consumer is of the smooth ambiguity type and derive efficient sharing rules. Heterogeneous ambiguity aversion leads to sharing rules that systematically differ from those in vNM-economies. The representative consumer's ambiguity aversion differs from that of the typical consumer; this leads to more compelling asset-pricing predictions. We focus on point-identified models but show that our insights extend to partially-identified models.
Keywords: D50; D53; D61; D81; 330; ambiguity sharing; model uncertainty; ambiguity aversion; identifiability; linear risk tolerance; pricing kernel